Characterization of Zebrafish Pax1b and Pax9 in Fin Bud Development. (13th August 2014) - Chen, Xuemei; Huang, Huizhe; Wang, Hua; Guo, Fengjin; Du, Xiaogang; Ma, Linqiang; Zhao, Liang; Pan, Zhuma; Gui, Haibo; Yuan, Taixian; Liu, Xin; Song, Lin; et al.
Abstract : Both Pax1 and Pax9 belong to the important paired box gene family (PAX), which mainly participates in animal development and sclerotome differentiation. To date, the precise molecular mechanism and related signaling pathway of Pax1 remain unclear. In our study, microinjection of morpholino- (MO-) modified antisense oligonucleotides against pax1b induced pectoral fin bud defects. Furthermore, we demonstrate that the phenotypes caused by the knockdown of Pax1b in zebrafish could not be phenocopied by pax9 MO and could not be rescued by either Pax1a or Pax9 overexpression. We further find that Pax1b affects the expression of col2a1, Uncx4.1, Noggin3, and aggrecan, confirming the role of Pax1b in chondrocyte differentiation and bone maturation. Moreover, we identify an interaction between PAX1 and FOXO1 and find that the interaction was enhanced under hypoxia stress. Together, this evidence for cell death caused by pax1b knockdown provides new insight into the role of the Pax protein family in cell fate determination and tissue specification.